2019
DOI: 10.1002/slct.201900687
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Co–Modified NixMgyO Solid Solutions for Hydrogen Production from Steam Reforming of Acetic Acid and a Model Blend

Abstract: This paper is focused on the Co‐modified NixMgyO solid solutions (10 wt% Ni, 2–6 wt% Co) for the steam reforming of acetic acid and a model blend. The pristine rocksalt structured NixMgyO solid solution and the modified NixMgyO−Co catalysts were synthesized via hydrothermal method and co‐impregnation. The activity of the catalysts was evaluated in the temperature range of 500–800 °C with a steam/carbon molar ratio of 3 and a gas hourly space velocity (GHSV) of 57,000 h−1. Low cobalt content (Co loading= 2 wt%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Mizuno et al 73 used Co‐Ni/MgAl 2 O 4 catalysts with S / C = 4 at 500°C achieving complete conversion but hydrogen selectivities around 62%. Luo et al 74 evaluate the influence of Co concentration (2‐6 wt%) over Ni x Mg y O catalyst, they led to the conclusion that in the acetic acid steam reforming at 600°C, S / C = 3, the best catalytic performance was achieved with 4 wt% of Co obtaining 79.4% of conversion with a hydrogen yield of 71%. Concerning Ni‐based catalysts, Hu et al 75 reported that 30Ni/Al 2 O 3 in the steam reforming of acetic acid with S / C = 3 at 400°C resulted in 70.9% of conversion with a hydrogen yield of 61.6%.…”
Section: Resultsmentioning
confidence: 99%
“…Mizuno et al 73 used Co‐Ni/MgAl 2 O 4 catalysts with S / C = 4 at 500°C achieving complete conversion but hydrogen selectivities around 62%. Luo et al 74 evaluate the influence of Co concentration (2‐6 wt%) over Ni x Mg y O catalyst, they led to the conclusion that in the acetic acid steam reforming at 600°C, S / C = 3, the best catalytic performance was achieved with 4 wt% of Co obtaining 79.4% of conversion with a hydrogen yield of 71%. Concerning Ni‐based catalysts, Hu et al 75 reported that 30Ni/Al 2 O 3 in the steam reforming of acetic acid with S / C = 3 at 400°C resulted in 70.9% of conversion with a hydrogen yield of 61.6%.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Currently, the main H 2 production methods are coal gasification, natural gas reforming, naphtha reforming, biomass utilization and water electrolysis. [7][8][9][10][11][12] H 2 production from fossil fuels is unsustainable and its production by water electrolysis is also suffered by high-cost and large energy consuming. However H 2 production from biomass can overcome these problems.…”
Section: Introductionmentioning
confidence: 99%